2010
DOI: 10.1002/emmm.201000107
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of FoxM1b leads to tumour metastasis

Abstract: The forkhead box M1b (FoxM1b) transcription factor is over-expressed in human cancers, and its expression often correlates with poor prognosis. Previously, using conditional knockout strains, we showed that FoxM1b is essential for hepatocellular carcinoma (HCC) development. However, over-expression of FoxM1b had only marginal effects on HCC progression. Here we investigated the effect of FoxM1b expression in the absence of its inhibitor Arf. We show that transgenic expression of FoxM1b in an Arf-null backgroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
139
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(145 citation statements)
references
References 49 publications
(69 reference statements)
5
139
1
Order By: Relevance
“…We also found that overexpression of Foxm1-⌬N alone or in the absence of one copy of tumor suppressor p19 ARF induced epithelial hyperplasia, but was insufficient to stimulate progression of epithelial hyperplasia to prostate adenocarcinomas. These data suggest that either a complete inactivation of p19 ARF , as was achieved in liver tumors (50), or deregulation of other tumorigenic pathways is necessary to promote oncogenic properties of Foxm1 in prostate epithelium. Consistent with this hypothesis, Foxm1 synergized with K-Ras (49) and ␤-catenin (39) to induce progression of lung and brain cancer, respectively.…”
Section: Foxm1 Requires For Prostate Carcinogenesismentioning
confidence: 80%
“…We also found that overexpression of Foxm1-⌬N alone or in the absence of one copy of tumor suppressor p19 ARF induced epithelial hyperplasia, but was insufficient to stimulate progression of epithelial hyperplasia to prostate adenocarcinomas. These data suggest that either a complete inactivation of p19 ARF , as was achieved in liver tumors (50), or deregulation of other tumorigenic pathways is necessary to promote oncogenic properties of Foxm1 in prostate epithelium. Consistent with this hypothesis, Foxm1 synergized with K-Ras (49) and ␤-catenin (39) to induce progression of lung and brain cancer, respectively.…”
Section: Foxm1 Requires For Prostate Carcinogenesismentioning
confidence: 80%
“…FOXM1 has been reported to play a central role in tumor metastasis (27)(28)(29), and few studies have explored the antitumor activity of thiostrepton. In our study, thiostrepton significantly decreased the migration and invasion capacity of Daoy cells.…”
Section: Discussionmentioning
confidence: 99%
“…FOXM1 play a critical role in tumor cell metastasis (27)(28)(29). Since tumor cell migration and invasion are essential steps in tumor metastasis, we further examined the effects of thiostrepton on cell migration and invasion in Daoy cells.…”
Section: Thiostrepton Impairs the Migration And Invasion Of Daoy Cellsmentioning
confidence: 99%
“…Interestingly, Zhang and colleagues injected the cells into the mammary gland fat pads formation of hepatocellular carcinoma in the absence of p19Arf, an endogenous inhibitor of FoxM1b. 39,40 Transgenic FoxM1b-p19Arf -/-cells reveal increased Akt-activity and increased Snail1 expression. Conversely, these cells express less E-cadherin and have an elevated Vimentin and α-SMA content, which documents that enhanced expression of FoxM1b results in changes in epithelial plasticity in dependence of p19Arf.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%